Study of the influence of methotrexate on bone metabolism - Bumeister , V.I.; Sikora , V.Z.; Riabenko , T.V.; Yarmolenko , O.S.; Dmytruk , S.M.; Kiptenko , L.I.; Ponyrko , A.O.; Teslyk , T.P. (Морфологія / Morphologia / Morfologìâ, 2024)
Actuality. The review highlights the peculiarities of the effect of methotrexate on the processes of physiological and reparative regeneration of bone tissue. Methotrexate is widely prescribed for the treatment of a large number of diseases, the course of which can be complicated by the occurrence of fractures. A feature of the use of the drug is a long period of prescription. Objective.To investigate the effect of methotrexate on the processes of physiological and reparative regeneration of bone tissue. Methods. A wide analysis of modern literary scientific data on the effect of methotrexate on the processes of physiological and reparative regeneration of bone tissue in scientific and metric databases PubMed, Web of Science, Google Scholar was carried out. Results. Treatment with methotrexate has a negative effect on the processes of physiological regeneration, which is manifested by the delayed formation of trabecular bone, increased resorption of bone tissue, the development of obesity in the bone marrow, and has an inhibitory effect on reparative regeneration, which is manifested by a delay in the formation of bone regenerate in the fracture area, a decrease in the mineralization of injured long tubular bones of the skeleton. Conclusion. Methotrexate slows down the processes of physiological and reparative regeneration, which with long-term use leads to the development of osteoporosis and delayed healing of bone fractures.